Pengembangan Motif Batik Etno Majaphit Pada Komunitas Pembatik Desa Lakardowo Kecamatan Jetis Kabupaten Mojokerto - Masnia Ningsih; Rakhmad Saiful Ramadhani (LPPM Stikosa - AWS, 2021)
The association of ethno majapahit batik craftsmen who are members of the “Lakardowo Village Batik Craftsman” community is an association which is engaged in the production of handicrafts / crafts. Until now, at the age of about four years, the community has the ability to produce quality products that have regional characteristics. However, this community has several obstacles in being able to compete with fellow batik craftsmen from outside the Mojokerto area, among others; can not yet emerge a characteristic that has a strong character to elevate batik ethno majapahit Mojokerto, does not have a patent for the design of the motif or trademark patent, so that in competing with batik craftsmen from areas outside Mojokerto are still not confident and have not received full trust from the market. With the Participatory Rural Appraisal (PRA) method, through intensive workshops by exploring the existing potential, namely developing ethno majapahit batik motifs, as well as facilitating partners to have patent rights for the motives they produce and also trademark patents registered with Menkumham. And equip ethno majapahit batik craftsmen with online marketing skills that allow them to relate to a wider range of consumers.